Polytechnic Education in the Distruption of Technology and Industrial Revolution 4:0 - Toyipur Toyipur (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2023)
The learning system in the majority of Polytechnics uses Blended Learning systems including face to face, practice / workshop and online with learning composition; 40% theory and 60% practice with industry link and match mechanisms. For industry link and match, a comprehensive policy between ministries is needed to determine the functional position of the Learning Technology Developer (PTP) as an integrated manager of the learning program in tertiary institutions especially the Polytechnic both various learning resources, methods, teaching materials, media and learning environments so that learning outcomes can increase the production of goods and services quickly, effectively and efficiently through meaningful, enjoyable learning. The method used in this research is "descriptive quantitative" because it describes, describes, and interprets the conditions, events, processes that are happening in the context of the problem. This research is intended to explore and clarify a phenomenon or social reality clearly. Online and conventional system learning methods or blended learning enable HR outcomes that are able to overcome technological disruption, on the other hand the hopes of the President and Menristekdikti that the ability to deal with the industrial revolution 4.0 in the era of technological disruption and globalization competition is not only through special abilities obtained because of completing master's education, master's degree in tertiary education which is said to produce responsive ability of industry 4.0 involvement but through improvement of learning culture. Indicator 0.033% of HR career as Developers of Learning Technology in tertiary institutions shows low regard for tertiary institutions in developing learning programs in the development of learning programs both the management of various learning resources, methods, media, teaching materials and learning environments according to the need for meaningful and enjoyable learning, this is caused by professional ego, sectoral ego.